Isolation and identification of pathogenic Fusarium oxysporum isolated from soybean leaves - I WAYAN SUANDA; I KETUT WIDNYANA; A. A. ISTRI MIRAH DHARMADEWI (Society for Indonesian Biodiversity, 2025)
Abstract. Suanda IW, Widnyana IK, Dharmadewi AAIM. 2025. Isolation and identification of pathogenic Fusarium oxysporum isolated from soybean leaves. Biodiversitas 26: 2261-2268. Not all fungi isolated from soybeans are pathogenic. Understanding the identity and pathogenicity of the fungi found is crucial for providing appropriate control recommendations, which can significantly impact soybean farming. This research aimed to compare the pathogenicity of various fungi isolates obtained from soybean plants with withering symptoms in fields in Bali, along with morphological and molecular identification. Five fungi isolates were chosen for the pathogenicity test, and the most aggressive isolate was further tested for morphological and molecular detection with PCR by using ITS1 and ITS4 primers. The pathogenicity test was performed by inoculating fungi into healthy soybeans from Anjasmoro, Argomulyo, and Argopuro cultivars, and the symptoms were assessed five days after inoculation. Five days after inoculation, the soybean leaves turned yellowish brown, the roots were few and short on all tested fungi isolates, while the uninoculated control seed remained asymptomatic. The five isolates were different in aggressiveness; the disease area percentage ranged between 81% and 98%, depending on the isolate. The most aggressive isolates inoculated in soybeans are the JKP2 and JKP3 isolates; the highest plant proportion inoculated by these isolates showed the most severe symptoms (the diseased area was 98% or complete plant rot). The JKP2 culture grown in PDA media is generally characterized by white to greenish purple, reverse white, and fluffy. At the same time, the mycelium of JKP3 isolate is white, reverse purple in the center, and white at the margins. Phylogenetic analysis confirmed the two isolates observed to be Fusarium oxysporum. To our knowledge, this is the first report of F. oxysporum isolated from soybeans in Bali.